Trends and Applications in Software Engineering Proceedings of the 7th International Conference on Software Process Improvement (CIMPS 2018) - Mejia, Jezreel; Muñoz, Mirna; Rocha, Álvaro; Peña, Adriana; Pérez-Cisneros, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers a selection of papers presented at the 2018 International Conference on Software Process Improvement (CIMPS 2018). CIMPS 2018 offered a global forum for researchers and practitioners to present and discuss the latest innovations, trends, findings, experiences and concerns in Software Engineering, embracing several aspects such as Software Processes, Security in Information and Communication Technology, and Big Data. Two of the conference's main aims were to support the drive toward a holistic symbiosis of the academic world, society, industry, government and business community, and to promote the creation of networks by disseminating the results of recent research in order to align their needs. CIMPS 2018 was made possible by the support of the CIMAT A.C., CUCEI (Universidad de Guadalajara, México), AISTI (Associação Ibérica de Sistemas e Tecnologas de Informação), and ReCIBE (Revista electrónica de Computación, Informática, Biomédica y Electrónica).
Keywords: Computational intelligence; Artificial intelligence; Sports sciences; Computational Intelligence; Artificial Intelligence; Sport Science